Antibacterial Activity Of Kenikir Flower Fractions (Cosmos caudatus Kunth) Against The Bacteria Staphylococcus aureus - Novia, Devi; Lestari, Gina; Ananda, Ananda (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Cosmos caudatus Kunth which is also known as kenikir is a traditional plant that is eaten as a vegetable and has medicinal properties. From previous studies it is known that kenikir leaves contain active antibacterial substances such as saponins, phenols, flavonoids, and tannins. However, kenikir flowers have not been found as antibacterial. So this study aims to determine how much kenikir flowers can inhibit the growth of Staphylococcus aureus bacteria. The disc paper diffusion method with a diameter of 6 mm was used in the antibacterial activity test. The concentrations used were 20%, 30%, 40% and using Clindamycin as an antibiotic. The test results were explained with descriptive analysis. From the study it can be concluded that the kenikir flower fraction (Cosmos caudatus Kunth) can inhibit the development of Staphylococcus aureus bacteria, the aquadest fraction got the best results at a concentration of 40% with an inhibition zone of 8.12 mm and the ethyl acetate fraction with a concentration of 40% produced an inhibition zone diameter of 9.9 mm.